A companion to Roman love elegy - Gold, Barbara K., 1945- (Malden, Mass. : Wiley-Blackwell, 2012)
A Companion to Roman Love Elegy is the first comprehensive work dedicated solely to the study of love elegy. The genre is explored through 33 original essays thatoffer new and innovative approaches to specific elegists and the discipline as a whole. Contributors represent a range of established names and younger scholars, all of whom are respected experts in their fieldsContains original, never before published essays, which are both accessible to a wide audience and offer a new approach to the love elegists and their workIncludes 33 essays on the Roman elegists Catullus, Tibullus, Propertius.
Front Matter -- Introduction / Barbara K Gold -- The Text and Roman Erotic Elegists. Calling out the Greeks: Dynamics of the Elegiac Canon / Joseph Farrell -- Catullus the Roman Love Elegist? / David Wray -- Propertius / W R Johnson -- Tibullus / Paul Allen Miller -- Ovid / Alison R Sharrock --, Book 3 / Mathilde Skoie -- Historical and Material Context. Elegy and the Monuments / Tara S Welch -- Roman Love Elegy and the Eros of Empire / P Lowell Bowditch -- Rome's Elegiac Cartography: The View from the / Eleanor Winsor Leach -- Influences. Callimachus and Roman Elegy / Richard Hunter -- Gallus: The First Roman Love Elegist / Roy K Gibson -- Stylistics and Discourse. Love's Tropes and Figures / Duncan F Kennedy -- Elegiac Meter: Opposites Attract / Llewelyn Morgan -- The Elegiac Book: Patterns and Problems / S J Heyworth -- Translating Roman Elegy / Vincent Katz -- Aspects of Production. Elegy and New Comedy / Sharon L James -- Authorial Identity in Latin Love Elegy: Literary Fictions and Erotic Failings / Judith P Hallett -- The in Roman Elegy / Alison Keith -- Patronage and the Elegists: Social Reality or Literary Construction? / Barbara K Gold -- Elegy, Art and the Viewer / Ȟrica Valladares -- Performing Sex, Gender and Power in Roman Elegy / Mary-Kay Gamel -- Gender and Elegy / Ellen Greene -- Approaches. Lacanian Psychoanalytic Theory and Roman Love Elegy / Micaela Janan -- Intertextuality in Roman Elegy / Donncha O'Rourke -- Narratology in Roman Elegy / Genevieve Liveley -- The Gaze and the Elegiac Imaginary / David Fredrick -- Late Antique Elegy and Reception. Reception of Elegy in Augustan and Post-Augustan Poetry / P J Davis -- Love Elegies of Late Antiquity / James Uden -- Renaissance Latin Elegy / Holt N Parker -- Modernist Reception / Dan Hooley -- Pedagogy. Teaching Roman Love Elegy / Ronnie Ancona -- Teaching Ovid's Love Elegy / Barbara Weiden Boyd -- Teaching Rape in Roman Elegy, Part I / Genevieve Liveley -- Teaching Rape in Roman Love Elegy, Part II / Sharon L James -- General Index -- Index Locorum.
Includes bibliographical references and indexes.
Keywords: Elegiac poetry, Latin -- History and criticism; Love poetry, Latin -- History and criticism; LITERARY CRITICISM -- Poetry; LITERARY CRITICISM -- Ancient & Classical; Civilization; Elegiac poetry, Latin; Love poetry, Latin; Rome -- Civilization; Rome (Empire); Electronic books; Criticism, interpretation, etc